The Urgency of the Bank's Notification Letter to the Customer for the Transfer of Receivables to Other Parties - Beny Anang Prihantoro; Elisatris Gultom (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Credit utilization to meet needs and support lifestyles carries potential negative consequences if individuals disregard the established terms and conditions. Often overlooked amidst increasing demand for credit are the associated costs, benefits, and risks of the credit product. Consequently, customers or consumers lacking adequate repayment capacity who allocate credit towards consumption exacerbate the issue of non-performing credit. Credit restructuring serves as a mechanism to alleviate borrowers' obligations to the Bank. However, the restructuring process is not invariably successful. Failure in restructuring efforts can contribute to a rise in Non-Performing Loans (NPL), thereby diminishing the quality of the Bank's assets.To mitigate NPL levels, a common strategy involves the transfer of bad debts through a cessie mechanism or the assignment of collection rights (receivables) from creditors to third parties. Cessie, however, can introduce challenges concerning the collection methods employed by these third-party assignees. Frequently encountered problems include the protection of consumers from unethical collection practices, the valuation of transferred receivables, and the potential for conflicts of interest between Financial Service Providers (PUJK) and third parties. The regulation of receivables transfer or collection rights within the financial services sector is addressed in the Financial Services Authority Regulation (POJK) Number 22 of 2023 concerning Consumer and Community Protection in the Financial Services Sector. Nevertheless, consumers frequently lodge complaints with the OJK regarding the absence of notification when PUJK transfers receivables to a third party. This lack of notification presents PUJK with a future reputational risk. Addressing this issue, this paper will examine the impact of a cessie conducted without a notification letter and propose a mechanism for submitting such notification, recommending its inclusion within the provisions of POJK Number 22 of 2023.